Paradigit Pododermatitis in Cattle: Literature review (Research, Society and Development, 2022)
Paradigit pododermatitis (PP) is inflammation of the second and fifth paradigits and the skin that surrounds them. Inflammation is usually accompanied by necrosis and loss of corneal substance. There are few reports about the disease, however it has been observed in animals raised extensively or semi-intensively in dirty pastures, recently deforested and with many stumps. Due to the economic losses caused, such as, for example, early disposal of animals from the herd and high losses in productivity, PP is extremely important in veterinary medicine. For this, a descriptive study was carried out through an indexed literature review on PP using online platforms such as Capes Periodicals, Science Direct, Scielo, Biblioteca Virtual em Saúde-MS, PubMed and PubMed Central. It is concluded that PP lesions are directly linked to animal management and welfare, emphasizing the importance of knowledge related to the epidemiology of the disease, with the aim of instituting effective control and prophylaxis measures.